Perencanaan Strategi TIK Proses Belajar Mengajar di Learning Center - Sunardi Sunardi; Dina Fitria Murad (ULTIMA InfoSys, 2017)
BINUS Center is the informal educational institution that organizes IT and language training. Inrecent years the revenue BINUS Center continues to decrease, it is evident from the outlet BINUS Center decreased from year to year. The purpose of making this research is to make strategy planning Business & ICT, create new models of learning supported by ICT strategy,test and measure the results obtained, and then made some strategic ideas at the moment and will come in the form of short-term priorities, medium and long term. The result is a cost that can be in the efficiency, a more flexible, first-class runs with a minimal number of participants, participant satisfaction, and competitive advantage. Keywords: business strategy, ICT strategy, business process improvement, priority.